Atributos físicos do solo e produtividade do milho sob sistemas de manejo e adubações - Costa, Monica S. S. de M.; Pivetta, Laercio A. [UNESP]; Costa, Luiz A. de M.; Pivetta, Laerte G. [UNESP]; Castoldi, Gustavo [UNESP]; Steiner, Fabio [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
No-tillage system is an efficient technique in control of soil erosion, when compared with conventional tillage, however, some studies indicate higher compaction under no-tillage, mainly in the surface layer. Strategies that increase the organic matter content, as crop rotation and organic fertilization, can be used to solve the soil compaction. The aim of this study was to evaluate the effect of soil managements (crop succession and crop rotation) and fertilization (organic, mineral and organic-mineral) in the physical properties of the soil, under no-tillage system, from 2006 to 2008. The evaluations were carried out in February 2007, after the summer corn harvest, and in September 2008, after the winter corn harvest. Crop rotation decreased the soil density and soil resistance to penetration and increased the macroporosity and total porosity. The use of organic sources of fertilization did not affect any of the physical attributes of soil. The yield of summer corn was highest in succession crop and mineral fertilization, however, in the winter, there was no difference between the soil managements and among the fertilizations.
Soil physical attributes and corn yield as affected by soil managements and fertilization
Keywords: soil compaction; rotation crops; organic fertilization